Батяня: [повесть] / Сергей Зверев - Зверев Сергей Иванович (Спецназ ВДВ, 2004)
Экземпляры: ф.15 (20220311) / Инвентарный номер: 54835 / Цена: 160.00 / Авт.знак: З-43 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6